2022
DOI: 10.52965/001c.38564
|View full text |Cite
|
Sign up to set email alerts
|

The use of antidepressants is linked to bone loss: A systematic review and metanalysis

Abstract: Introduction Depression and antidepressants are among risk factors for osteoporosis. However, there are still inconsistencies in literature regarding bone consequences of antidepressant drugs and the role of age and the natural decline of bone health in patients with depression. Objective To investigate the relationship between antidepressant and bone mineral density (BMD). Methods We conducted a systematic review and metanalysis according to PRISMA guidelines searching on PubMed/Medline, Cochrane Database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…324 A recent review and metanalysis observed a significant decrease in bone mineral density after using SSSRIs with a mean effect of 0.28 (95% CI = 0.08, 0.39). 313 A retrospective comparison did not show a significant difference in the time of bone fractures to union between patients with chronic SSRI use and patients who had not been on SSRIs (time to heal 6.1 vs. 6.0 months). 323 Daily use of SSRIs in adults over 50 years was associated with a twofold increased risk of clinical fragility fracture, lower bone mineral density at the hip, and a trend toward lower bone mineral density at the spine.…”
Section: Selectiveserotoninreuptakeinhibitorsmentioning
confidence: 87%
See 3 more Smart Citations
“…324 A recent review and metanalysis observed a significant decrease in bone mineral density after using SSSRIs with a mean effect of 0.28 (95% CI = 0.08, 0.39). 313 A retrospective comparison did not show a significant difference in the time of bone fractures to union between patients with chronic SSRI use and patients who had not been on SSRIs (time to heal 6.1 vs. 6.0 months). 323 Daily use of SSRIs in adults over 50 years was associated with a twofold increased risk of clinical fragility fracture, lower bone mineral density at the hip, and a trend toward lower bone mineral density at the spine.…”
Section: Selectiveserotoninreuptakeinhibitorsmentioning
confidence: 87%
“…312 As osteoblasts and osteoclasts have receptors for serotonin and can be exposed to this substance by autocrine, paracrine, or endocrine pathways, the levels of serotonin can affect bone metabolism. [313][314][315] Most of the in vitro studies found serotonin to exert a positive effect on osteoblast proliferation, differentiation, and mineralization [316][317][318] while others reported inhibitory effects on osteoblastic cells. [319][320][321] In detail, a study in rats found that low levels of serotonin inhibited osteoblast proliferation, differentiation, and mineralization whereas this role was mitigated at high 5-HT concentrations.…”
Section: Selectiveserotoninreuptakeinhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, SSRIs are the most safe and commonly prescribed class of antidepressants, making them the first-line treatment for older patients due to their limited effects on autonomic system activity and a lower impact on blood pressure [ 285 ]. Nevertheless, SSRIs may be associated with falls and osteoporosis [ 286 ].…”
Section: Effect Of Aging Diseases and Their Treatment On The Redox Ba...mentioning
confidence: 99%